Mediation effects of cognitive, physical, and motivational reserves on cognitive performance in older people - Cabaco, Antonio Sánchez; Wobbeking Sánchez, Marina; Mejía-Ramírez, Manuel; Urchaga-Litago, José David; Castillo-Riedel, Eduardo; Bonete-López, Beatriz (Frontiers in Psychology, 2023)
Introduction We study from a multidimensional perspective the different factors that help prevent the development of cognitive impairment in old aging. Methods This study analyzed in 300 elderly subjects the relationship between cognitive reserve (CR), physical reserve (PR) and motivational reserve (MR) with cognitive impairment. This study also takes into consideration different variables (sex, age, educational level, and institutionalization) that might affect the results in the different types of reserves (CR, physical and MR) and cognitive impairment. Results The results show that people with a higher cognitive reserve, physical reserve and motivational reserve have less cognitive impairment. Discussion Therefore, it is important to consider measuring the CR as a variable to diagnose neurodegenerative illnesses but it is also essential to consider the physical state and physical activity, as well as the motivational dimension. With the cognitive reserve and sex variables no significant differences were observed. Age had a negative effect on strategic flexibility, but those with higher CR had better cognitive flexibility and the educational.